Investigating factors that affect job satisfaction and life satisfaction - KIM, Yoo Jeong (KDI School, 2019)
‘Geographical relocation’ has been conducted to alleviate overcrowding and support balanced regional development in many countries. Recently, in Korea, the ongoing policy of relocating public organizations and building innovative cities were implemented in 2004 when the ‘Special Act on Balanced National Development’ was enacted. As of 2018, there were a total of 154 public institutions relocated. At a time when the effectiveness of the relocation should be measured, there has been little prior researches addressing job satisfaction and life satisfaction of relocators in the public sector in Asia. Thus, the aim of the study was to examine the determinants of job satisfaction and life satisfaction and correlation between the two different satisfactions. The study presented here investigated the following research questions: i) Does working conditions in the new workplace affect job satisfaction?; ii) Does interactivity in the new workplace affect job satisfaction?; iii) Does the social infrastructure in the new location affect life satisfaction?; iv) Does social activity in the new location affect life satisfaction?; v) Is there a correlation between job satisfaction and life satisfaction? The study collected data through an online survey and applied statistical analysis using factor analysis, regression, and ANOVA. The result of analysis support that of working condition variables, work system and development opportunity affect job satisfaction, and interactivity such as building relationship and building trust affect job satisfaction. When it comes to life satisfaction, both social infrastructure and social activity are influential factors. There was a positive correlation between job satisfaction and life satisfaction. The current study provides implications theoretically and managerially for future research on satisfaction of employees in the public sector in case of relocation.
Thesis(Master) --KDI School:Master of Public Management,2019